Shen-Qi-Jiang-Tang granule ameliorates diabetic nephropathy via modulating tumor necrosis factor signaling pathway. (1st March 2023) - Chen, Miao-miao; Jia, Jin-hao; Tan, Yu-jun; Ren, Yu-shan; Lv, Jun-lin; Chu, Ting; Cao, Xin-yue; Ma, Ru; Li, De-fang; Zheng, Qiu-sheng; Liu, Zhong; Li, Jie
Abstract: Ethnopharmacological relevance: Shen-Qi-Jiang-Tang granule (SQJTG), a classic traditional Chinese medicine (TCM) prescription, has been widely used in clinical for diabetes, especially type Ⅱ diabetes. Previous anti-diabetic studies stumbled across that SQJTG has a potential kidney protective effect on diabetic nephropathy (DN). However, the protective mechanism of SQJTG on DN still needs to be explored. Aim of the study: The purpose of the present study was to explore the therapeutic effect of SQJTG on DN through both bioinformatics analysis and in vivo experiments. Methods and materials: The TCMIP database was used for screening potential compounds and targets of SQJTG, and the GeneCards, OMIM, DrugBank, and TTD databases were used for collecting DN-related genes. Then protein-protein interaction analysis for the common targets of SQJTG and DN was performed by the STRING database. Meanwhile, KEGG and GO were carried out using the Metascape and DAVID databases. In vivo experiments, to testify the potential kidney protective effects of SQJTG, STZ-induced DN mice with different dosages of SQJTG treatment were collected and the renal tissues were detected by H&E, PAS, Masson and TUNEL staining. Immunohistochemistry and immunoblotting were used to assess the proteins' expressions. Flow cytometry and ELISA assay were used to detect the levels of pro-inflammatory cytokines. Results: Among the 338 compounds ascertained by SQJTG, there were 789 related targets as well. Moreover, 1, 221 DN-related targets were predicted and 20 core targets were screened by the PPI analyses. According to GO and KEGG pathway analysis, SQJTG may affect DN via the TNF pathway. For the in vivo experiments, renal histomorphological examinations demonstrated that SQJTG treatment significantly ameliorated STZ-induced kidney damage and had a dosage dependence. Meanwhile, mice with DN were found to have dramatic increases in IL-1, TNF-α, IL-6, and IL-12, but markedly decreased after administration of SQJTG. In addition, the protein levels of TNF signaling molecules, like p-P65, p-JNK, and p-p38, showed significantly elevated in kidney tissues of DN mice and attenuated after SQJTG treatment. Conclusions: SQJTG exerts a kidney protective effect in DN mice via modulating TNF signaling pathways, and it has promising applications for the treatment of DN. Graphical abstract: Image 1 Highlights: 338 compounds ascertained from SQJTG targeted 789 genes and 133 genes were diabetic nephropathy (DN)-related. GO and KEGG pathway analysis predicted that SQJTG may affect DN via TNF pathway. In vivo, SQJTG significantly ameliorated STZ-induced kidney damage via inhibited IL-1, TNF-α, IL-6, and IL-12 levels. SQJTG relieved STZ-activated TNF signaling pathway by down-regulated p-P65, p-JNK, and p-p38 expressions in STZ-mice.